Analisis Persamaan dan Perbedaan Bahasa-Bahasa Nusantara dalam Konteks Budaya di SD - Raudahtul Feby Diani; Silvina Noviyanti; Nazurty; Yuyun Arofah; Harnita Risnawati; Nikita Adewina (STKIP Subang, 2026)
This study examines the similarities and differences of Nusantara languages within a cultural context. Indonesia is known for its rich linguistic diversity, where each regional language reflects the identity, values, and local wisdom of its speakers. The purpose of this research is to analyze how these languages share common features while also demonstrating distinct characteristics influenced by cultural backgrounds. This study employs a qualitative approach using a literature review method, collecting data from books, scientific journals, and relevant research articles. The findings indicate that Nusantara languages exhibit similarities in basic vocabulary, sentence structure, and cultural expressions, which suggest historical connections and shared cultural values. However, significant differences are found in phonology, lexicon, and grammatical systems, shaped by geographical conditions, social interactions, and cultural developments. Furthermore, language plays a crucial role in preserving cultural heritage, including traditions, norms, and oral literature. In the era of globalization, the use of regional languages is declining, particularly among younger generations, posing a threat to their sustainability. Therefore, efforts such as education, documentation, and the use of digital media are essential for language preservation. This study highlights the importance of understanding linguistic diversity as a means to strengthen cultural identity and promote mutual respect among different communities in Indonesia. Keywords: Nusantara languages, linguistic comparison, cultural context, language diversity